Integrated guide for public procurement and private contracts of collective catering system and SDGs. (13th November 2019) - Barocco, G; Patussi, V; Cella, M; Germano, D; Pernarcic, A; Longo, T; Occoni, E; Steinbock, D; Calabretti, A
Abstract: : Surveys (2008-2018) carried out by the Local Health Agency of Trieste (ASUITS) in local collective catering (CC) services of schools, hospitals, nursing homes, and workplaces (25.000 daily meals) have shown some non - adherence to healthier food choices, food standards, procedures and green and social procurement as recommended by the WHO, FAO, UE, Ministry of Health and of Environment. The purpose of this project is to support local public and private organizations in transforming the national and regional catering services food standards related to health, nutrition, environment and social criteria into food procurement and food contracts specifications. This has been done by compiling the major obstacles to improved standards observed during surveys, and by sharing critical and relevant examples with major public contractors across local, regional and national level. The guidelines (GL) for public procurement of CC consist of five chapters: the elaboration of specifications; a response module to present the offer of services; selection and award criteria, an evaluation system of offers, and the technical specifications attached. Technical information fixes the constituent elements of the service in order to have similar and directly comparable offers. GL cover both the purchasing of food and the contracting of catering services. In this way public or private institutions are able to prepare tender documents suitable to respond to health, economic needs and Sustainable Development Goals (SDGs). The development of the GL has increased the awareness and real potential that local organizations have in enhancing the strategic use of purchasers to boost food qualification, jobs, growth and investment. As well as to create a more innovative economy, to be resource and energy efficient, and to be socially-inclusive. To meet population nutrient intake goals and SDGs it is necessary to increase co-operation and the sharing of the objectives of 'Health in All Policies'. Key messages: Contractors need practical tools to apply sustainable development goals criteria in collective catering. The integrated collective catering guide is a key to improving capacity building in institutions.